A169 DEVELOPMENT OF A DECISION TOOL TO IMPROVE UTILISATION OF RECOMMENDED SURVEILLANCE INTERVALS FOR INDIVIDUALS WITH COLORECTAL POLYPS: A FOCUS GROUP ANALYSIS. (26th February 2020) - Lee, E; Singh, H; Simms, A; Restall, G; Shafer, L; Walker, J; Park, J
Abstract: Background: Several studies have demonstrated a high utilization of colonoscopy at shorter and longer time intervals than guideline recommendations. Innovative methods are required to increase adherence to recommended timing. Aims: 1) Explore current approaches used by endoscopist (EPs) and primary care providers (PCPs) to determine and communicate colonoscopy surveillance intervals (SI) between EPs, PCPs, and patients. 2) Obtain feedback for refining a decision tool to facilitate recommended SI. 3) Determine participant agreement of recommended SIs with current guidelines. Methods: We conducted 4 focus groups (FGs); 3 FGs included EPs (n=12) and EPs in training (n=6); 1 FG included PCPs (n=4). FG questions explored use of guidelines, communication and follow-up practices with PCPs, EPs and patients, and challenges to follow-up. Participants were also asked for feedback about a prototype polyp SI decision tool that was developed using an algorithm synthesizing current Canadian Association of Gastroenterology, US Multisociety Task Force, and expert panel guidelines on SI. FGs were audio-recorded and transcribed for qualitative content analysis. FGs were analysed separately, then compared for similarities and differences. Finally, participants individually made interval recommendations for 7 common endoscopy scenarios. Responses were analyzed for agreement with the guidelines used to develop the decision tool. Results: EPs reported not routinely referring to guidelines and were confident in their memory of the intervals although some reported checking occasionally. Many indicated they may use the tool in a web based or mobile application for more complicated scenarios, although some would never use it. Concerns regarding the tool included being up to date with research evidence and having required data to input on hand. PCPs reported the tool may be useful as a communication aid to involve patients in decision making. A challenge noted in all FGs was role confusion regarding communicating, tracking, and scheduling patients' future procedures on time. Analysis of EPs (n=9) responses to the 7 scenarios showed that percent agreement with guidelines was low: 44% scored below 50% correct. Participants with the highest agreement scored 6/7; responses with the lowest agreement scored 0/7. The most common score was 3/7. Conclusions: EPs appeared to be overconfident in their recommendations, but many were open to trying a website or mobile application decision tool to make evidence-based colonoscopy SI recommendations. Understanding, among PCPs and EPs, regarding responsibility for communicating results and scheduling follow-up surveillance for patients was inconsistent. Participant feedback informed development of a mobile application that is currently being pilot tested. Funding Agencies: Research Manitoba